Stress exposure due to the COVID-19 pandemic on menstrual abnormalities: A systematic review - Nugroho, Salsabila Bestari; Utomo, Budi; Frety, Endyka Erye; Sa'adi, Ashon; Fauziyah, Shifa (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS There is a significant higher level of stress during COVID-19 pandemic. The highest menstrual abnormalities during pandemic cases were found in premenstrual syndrome and dysmenorrhea, and the lowest was found in menstrual cycle disorders (polygomenorrhea, oligomenorrhea, amenorrhoea).   ABSTRACT Objective: COVID-19 pandemic had caused a considerable increase in stress level due to reduced human mobility, interaction, and activity. High stress levels are often associated with an adverse health outcome. Stress influences female reproduction systems, where it is an important indicator of female health. This systematic review aimed to analyze the relationship between stress levels due to the COVID-19 pandemic and the incidence of abnormal menstruation. Materials and Methods: This systematic review was registered in PROSPERO international database (CRD42023433296). Literature search was conducted across four databases, Pubmed, Web of Science, Science Direct, and Google Scholar, with boolean AND and OR operators as keyword search assistants. Literature was searched and limited to journals published during the pandemic (2019-2023), written in English, an open access article, and meet the keywords. Literature not a research study, duplicated and limited access were not included. Inclusion to the journal was carried out by screening using PRISMA flowchart and EPHPP Assessment Tool for Quantitative Studies for the quality assessment. Results: Nine out of 1150 journals were eligible for review. Seven studies revealed that there was a significant relationship between stress and anxiety due to the COVID-19 pandemic and the incidence of menstrual abnormalities. However, one study revealed that these changes were not significant. Conclusion: There is a significant relationship between stress during the COVID- 19 pandemic and the incidence of menstrual abnormalities.